Design of pipeline leakage monitoring system for coal mine - ZHAO Lin; WANG Jiqiang; HOU Moyu (Gong-kuang zidonghua, 2016)
For problems existed in manual inspection method of pipeline running monitoring in coal mine underground such as laborious consumption, time consumption, difficult leak point detection under sudden conditions and so on, a pipeline leak monitoring system for coal mine was designed which was based on optical fiber sensing technology and negative pressure wave signal detection and location principle. Structure of the system was introduced as well as key technologies including enhancement sensitivity structure of fiber pressure sensor and accurate acquisition technology of negative pressure wave falling edge signal. Long-time running test and reliability test of the system were taken out. The test results show that the system can identify normal operation status of valve and pump, and locate pipeline leakage point under sudden condition with location error of less than 1%, which has stable and reliable operation.